Heat Shock Protein–Peptide Complexes, Reconstituted In Vitro, Elicit Peptide-specific Cytotoxic T Lymphocyte Response and Tumor Immunity - Blachere, Nathalie E. (The Rockefeller University Press, 1997)
Heat shock protein (HSP) preparations derived from cancer cells and virus-infected cells have been shown previously to elicit cancer-specific or virus-specific immunity. The immunogenicity of HSP preparations has been attributed to peptides associated with the HSPs. The studies reported here demonstrate that immunogenic HSP–peptide complexes can also be reconstituted in vitro. The studies show that (a) complexes of hsp70 or gp96 HSP molecules with a variety of synthetic peptides can be generated in vitro; (b) the binding of HSPs with peptides is specific in that a number of other proteins tested do not bind synthetic peptides under the conditions in which gp96 molecules do; (c) HSP–peptide complexes reconstituted in vitro are immunologically active, as tested by their ability to elicit antitumor immunity and specific CD8(+) cytolytic T lymphocyte response; and (d) synthetic peptides reconstituted in vitro with gp96 are capable of being taken up and re-presented by macrophage in the same manner as gp96– peptides complexes generated in vivo. These observations demonstrate that HSPs are CD8(+) T cell response–eliciting adjuvants.